PENERAPAN KURIKULUM MERDEKA BELAJAR PADA PENDIDIKAN ANAK USIA DINI - Munawaroh, Hikmah; Kuswantono, Sri; Faradiba, Yasmin; Jahja, Yudrik (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract The current government policy in ECCE institutions has used an independent learning curriculum. The problems that arise educators do not have sufficient capacity in developing learning tools in the independent curriculum. The solution to this problem is in the form of a workshop on the development of ECCE learning tools in the independent curriculum. The method or approach offered to solve partner problems is training and hybrid workshop. The implementation begins with conducting an initial needs analysis through interviews and discussions. Then proceed to the preparation process stage, namely making a questionnaire about the right way to develop learning tools in the independent curriculum. The next stage is the implementation, implementation of socialization carried out in a hybrid manner (on-site workshops and online via the zoom application). Next is mentoring, which is carried out to see the improvement of ECCE educators in the development of learning tools in the independent curriculum. The success of this activity can be seen by the increasing knowledge of ECCE educators about the development of ECCE teaching tools in the independent curriculum. The results obtained were 100% of this activity was useful for increasing knowledge about the application of the independent curriculum, 100% of this activity was well facilitated by the committee, 100% of the material was easy to understand, 100% of the media presented was interesting, 100% of participants got new knowledge, 100% of the material could be implemented in ECCE institutions, 84.5% of the workshop activity time was fulfilled. Abstrak Kebijakan pemerintah saat ini dilembaga PAUD telah digunakan kurikulum merdeka belajar. Permasalahan yang muncul pendidik belum punya kapasitas yang cukup dalam mengembangkan perangkat pembelajaran pada kurikulum merdeka. Solusi untuk permasalahan tersebut berupa workshop pengembangan perangkat pembelajaran PAUD pada kurikulum merdeka. Metode atau pendekatan yang ditawarkan untuk menyelesaikan permasalahan mitra yaitu pelatihan dan worshop secara hybrid. Pelaksanaan diawali dengan melakukan analisis kebutuhan awal melalui wawancara dan diskusi. Kemudian dilanjutkan ke tahap proses persiapan, yaitu membuat kuesioner tentang cara yang tepat untuk pengembangan perangkat pembelajaran pada kurikuum merdeka. Tahap selanjutnya adalah pelaksanaan, pelaksanaan sosialisasi yang dilakukan secara hybrid (workshop langsung di tempat dan online melalui aplikasi zoom). Selanjutnya adalah pendampingan, yang dilakukan untuk melihat peningkatan pendidik PAUD dalam pengembangan perangkat pembelajaran pada kurikulum merdeka. Keberhasilan kegiatan ini dapat dilihat dengan meningkatnya pengetahuan pendidik PAUD tentang pengembangan perangkat pembejaran PAUD pada kurikulum merdeka. Hasil yang didapat adalah 100% kegiatan ini bermanfaat untuk meningkatkan pengetahuan tentang penerapan kurikulum merdeka, 100% kegiatan ini difasilitasi dengan baik oleh panitia, 100% materi mudah dipahami, 100% media yang disajikan menarik, 100% peserta mendapat pengetahuan baru, 100% materi dapat diimplementasikan di lembaga PAUD, 84,5% waktu kegiatan workshop tercukupi.